Disability studies in Hungary - Kemény, Peter (Socialno delo, 2014)
The paper, following the train of thought of the UN Convention on the Rights of Persons with Disabilities, is focusing on the development of disability studies in Hungary. Although Hungary was one of the first countries to ratify the UN Convention on the Rights of Persons with Disabilities (2007), the humanrights' based approach is still very weak, due to the weakness of the civil organisations, deficiencies of political democracy, and the party politics dominated permanent transition of the Hungarian welfare state. Disability studies, characterised internationally by the initiative of the disabled persons themselves, were in Hungary, however, a top-down process initiated by researchers and experts. This is reflected in the controversies and slowness of the deinstitutionalisation process, in the dominance of large institutions and in the exclusion of disabled adults from the labour market, instead of the implementation of community based solutions. Governmental approaches and policies are first and foremost targeting economic objectives, e.g. to decrease the budgetary deficit even at the expense of the living conditions of disabled people. The official rhetoric and the organisational solutions have not broken away from the medical model of disability yet.
Keywords: človekove pravice; human rights; civil society; civilna družba; zaposlovanje; neodvisno življenje; dezinstitucionalizacija; hendikep; Hungary; Madžarska; visokošolski študij